THE BIOPHYSICAL CHARACTERISTICS AND STRUCTURAL EXPLORATION OF PROGRAMMED CELL DEATH REGULATOR B-CELL LYMPHOMA 2-ASSOCIATED X PROTEIN OF CHINESE LIVER FLUKE (CLONORCHIS SINENSIS) - Panda, Subhamay; Prasad, Dipak; Bag, Indranil (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Objective: The balance between deaths and cellular life is regulated by B-cell lymphoma 2 (BCL-2)-associated X protein (BAX) an important pro-apoptotic components of BCL-2 family. With this initial point, the aim of this study was to determine a comparative composite based structure of BAX of Chinese liver fluke and different structural analysis. Methods: Protein amino acid of BAX of Chinese liver fluke mined from National Centre for Biotechnology Information (http://ncbi.nlm.nih.gov). Molecular model of BAX of Chinese liver fluke protein was generated by the comparative composite modeling tool Iterative Threading ASSEmbly Refinement suite. Afterward, I-TASSER generated molecular model was subjected to further structural improvements by energy minimization step. Distribution of negatively and positively charged amino acid over molecular modeled structure, distribution of secondary structural elements, and hydrophobicity molecular surface analysis was performed with the help of bioinformatical tools. Results: Analysis of Ramachandran plot created by PROCHECK tool is a consensus standard for validation purpose of protein structural modeling. Altogether 97.8% of the residues were detected in allowed and favored regions, which in turn validate the quality of generated protein structural model. Total negatively and positively charged residues within the BAX of Chinese liver fluke were 23 and 20, respectively. Chimera package-guided hydrophobicity molecular surface analysis illustrates that molecule specific hydrophobicity surface is exclusive to BAX protein molecule. Conclusion: Within the scope of this scientific investigation, we have successfully utilized molecular modeling approach to suggest the first molecular three-dimensional model structure of BAX of Chinese liver fluke. The synchronous balance between cellular deaths and cellular life is keeping up by BAX, an important pro-apoptotic family member of BCL-2 family. Consequently, it would be an exciting approach to resolve its structural characterization and molecular structure to propose mode of mechanism action. Â